2010
DOI: 10.1586/erc.10.53
|View full text |Cite
|
Sign up to set email alerts
|

Interventional management of atrial fibrillation

Abstract: Atrial fibrillation (AF) is the most common arrhythmia seen in clinical practice, and is associated with increased morbidity and mortality. Management of AF is challenging due to the modest efficacy of antiarrhythmic drug therapies, some of which have significant adverse effects or toxicity. Nonpharmacological treatment of AF, including AF ablation, has recently evolved as an attractive, efficacious and potentially 'curative' therapeutic modality in selected patients. This article reviews various interventiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
0
2
0
1
Order By: Relevance
“…Вместе с тем следует отметить, что в подавляющем большинстве исследований для достижения такой эффективности лечения у 25-35 % больных потребовалось проведение повторной, а в некоторых случаях и третьей операции РЧА [2,5,7,8]. Кроме того, всем пациентам в послеоперационном периоде для усиления эффекта назначались антиаритмические препараты I-III классов по классификации E. Vaughan Williams и D. Harrison (или их комбинации).…”
Section: For Citation: Linchak R M Nedbaykin a M Komkov D S unclassified
“…Вместе с тем следует отметить, что в подавляющем большинстве исследований для достижения такой эффективности лечения у 25-35 % больных потребовалось проведение повторной, а в некоторых случаях и третьей операции РЧА [2,5,7,8]. Кроме того, всем пациентам в послеоперационном периоде для усиления эффекта назначались антиаритмические препараты I-III классов по классификации E. Vaughan Williams и D. Harrison (или их комбинации).…”
Section: For Citation: Linchak R M Nedbaykin a M Komkov D S unclassified
“…Atrial fibrillation (AF), the most common sustained arrhythmia in clinical practice, has become a major epidemic in cardiovascular medicine and is associated with increased morbidity and mortality . AF is often difficult to manage, especially in the elderly with persistent or permanent AF, because safe and effective antiarrhythmic drugs are lacking . In AF patients with rapid ventricular rates and symptoms refractory to drug therapy, atrioventricular junction (AVJ) ablation and cardiac pacing is a proven effective therapeutic option .…”
Section: Introductionmentioning
confidence: 99%
“…Management of AF is challenging because of the modest efficacy of antiarrhythmic drugs, many of which have considerable adverse effects. 2 Moreover, studies have reported AF recurrence rates of 50%-60% over a mean of 1-2 years. 3,4 However, in patients with AF and a fast ventricular rate, radiofrequency catheter ablation of the atrioventricular node (AVN) and implantation of a permanent pacemaker is an effective therapeutic strategy, especially for elderly patients with permanent AF 5 and for highly symptomatic patients with AF refractory to pharmacologic therapy.…”
Section: Introductionmentioning
confidence: 99%